Factors affecting the performance of Klang Valley mass rapid transit project-study on improving the project performance - Arivahnathan, Pandiyan (2014)
Economic and social development of a country largely depends on the development of infrastructure facilities. In other words, infrastructures development is considered as the backbone of a nation. As for Malaysia, Kiang Valley Mass Rapid Transit Sungai BulohKajang line is very important project as it will be a first step forward in placing Kuala Lumpur among the top cosmopolitan and most liveable cities in the world. Identification of the factors affecting the performance of these Kiang Valley Mass Rapid Transit project is very crucial in improving the productivity of overall construction work. Therefore, the aim of this research is to study the factors affecting the performance of Klang Valley Mass Rapid Transit Project and mitigation approach that have should taken by the IVIRT Corp to improve project performance. The study is basically carried out by distributing the questionnaires to MRT Corp. Meanwhile, Relative Importance Index (Ril) method was adapted to analyses the data gathered from questionnaire survey. From the result, it can be concluded that client satisfaction factors, time factors, quality factors, cost factors and environment factors are the five main major groups of factors that largely influence the performance of Klang Valley Mass Rapid Transit project. The study also gives some beneficial recommendations for the construction team players, for them to improve the overall project performance.